Unidentified Built- Heritage of Historic Siddhapur (Sehore), Madhya Pradesh, India - Deeksha Singh (Calibrating Urban Livability in the Global South, 2024)
Sehore, the administrative center of Sehore district in Madhya Pradesh, is situated at the foothills of Vindhyachal ranges on the eastern part of the Malwa plateau. Rich in historical significance, Sehore witnessed its peak during the 18th and 19th centuries, becoming a pivotal hub for trade, religion, and military affairs. Siddhapur, historically a seat for Saiva, Shakti, Vaisnava, and Jain priests for over 2000 years, gained prominence under the Marathas of Peshwas in the early 18th century, flourishing as a center for art, literature, and education. The town played a crucial role during the Revolt of 1857 and hosted India’s first war of independence in 1824. The architectural heritage of Sehore holds substantial cultural value, reflecting diverse historical layers. Examining the town’s expanding nature and the subsequent loss of historicity, the research goals address the lack of organization in Sehore’s development, which has led to the deterioration of existing heritage structures. The town’s rapid expansion necessitates urgent planning, with heritage resources forming a critical aspect. Identifying, listing, and documenting the built heritage is crucial for safeguarding the historical and cultural legacy of the town, ensuring its future development and preservation. The purpose of the research is to physically survey the town’s built heritage, map it, and evaluate its architectural style. This approach aims to provide a thorough grasp of the anthropological, historical, and geographical elements that characterize the Sehore’s setting in order to serve as the foundation for a management and conservation strategy.